HUBUNGAN PENGETAHUAN, POLA TIDUR, POLA MAKAN, INHIBITOR, DAN ENHANCER DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI PONDOK PESANTREN AL-AMANAH AL-GONTORY TAHUN 2023 - Kania Noviyanti Handini (2023)
The prevalence of adolescents with anemia in Indonesia in 2018 is around 32%. The group of young women is ten times more likely to experience anemia problems than young men. Anemia problems can be influenced by knowledge, sleep patterns, diet, inhibitors, and enhancers. This study aims to determine the relationship between knowledge, sleep patterns, eating patterns, inhibitors, and enhancers with the incidence of anemia in young women at Al-Amanah Al-Gontory Islamic Boarding School. This study used a cross-sectional design with 113 samples selected using a stratified random sampling technique. Data analysis used the Chi-Square test and Fisher's Exact. The results of the analysis showed that there was a relationship between sleep patterns (p=0.003), protein intake (p=0.000), iron intake (p=0.000), and inhibitors (p=0.000) and the incidence of anemia and there was no relationship between knowledge (p = 0.156) and enhancer (p = 0.970) with the incidence of anemia. This study concludes that there is a relationship between sleep patterns, protein intake, iron intake, and inhibitors with the incidence of anemia and there is no relationship between knowledge and enhancers with the incidence of anemia in female adolescents.